Experimental chemotherapy with combinations of ergosterol biosynthesis inhibitors in murine models of Chagas' disease. - Maldonado, R A (1993)
We report the effects of ketoconazole and the bistriazole ICI 195,739 acting alone or in combination with the allylamine terbinafine (Lamisil) on murine models of Chagas' disease. Mice infected with 10(5) Trypanosoma (Schizotrypanum) cruzi blood trypomastigotes and treated orally with 30 mg of ketoconazole per kg of body weight per day for 7 days, starting at 24 h postinoculation, had 100% survival after 35 days, while controls (untreated) or animals that received 15 mg of ketoconazole or 100 mg of terbinafine per kg/day by the same route had 0% survival after the same period of time. However, all mice receiving the combination of 15 mg of ketoconazole plus 100 mg of terbinafine per kg/day survived for 35 days after infection; it was shown that the survival of the animals treated with this combination was statistically greater than that obtained with either drug acting alone and was indistinguishable from that observed with the high doses of ketoconazole, indicating a synergistic action of the drugs in vivo. However, most animals that survived after the 7-day treatments were not cured, as indicated by a delayed but persistent parasitemia. When the treatment was extended to 14 days, 100% survival was obtained 10 weeks after inoculation for mice treated with 30 mg of ketoconazole per kg/day and the combination of 15 mg of ketoconazole per kg/day plus 100 mg of terbinafine per kg/day, while two-thirds of the mice treated with 15 mg of ketoconazole per kg/day alone were alive after the 14-day treatment; controls or animals that received 100 mg of terbinafine per kg/day did not survive after 25 days. Parasitemia in all surviving mice was negative after 55 days but parasitological cure, as assessed by subinoculation of organs in naive animals, was predominant only in animals that received the combined drug treatment. We also investigated the bistriazole ICI 195,739 and found, as reported previously, that just 1 mg of the compound per kg/day administered orally for 5 days was enough to protect most mice from death 30 days after inoculation, but no parasitological cures were observed. However, in the protocol used in the present study, the protective activity of ICI 195,739 at suboptimal doses (0.5 mg/kg/day) could be enhanced when it was used in combination with terbinafine at doses of the allylamine that by themselves induced no significant protection. Survival of the mice was inversely correlated with the levels of parasitemia in all cases. Extension of the treatment period with the triazole to 15 days at 1 mg/kg/day afforded definitive protection against death, with parasitological cure being achieved in 50% of mice at 10 weeks postinoculation, but no enhancement of its activity at suboptimal doses was observed when it was used in combination with terbinafine during this extended observation period. Taken together, these results supports the proposition that ketoconazole used in combination with terbinafine could be useful in the treatment of humans with Chagas' disease because it can promote parasitological cure without the need to resort to the use of high levels of the azole, which is known to interfere with hepatic function and steroid synthesis in the host. They also support the conclusions of previous in vitro studies which suggested that the triazole ICI 195,739 blocks the proliferation of T. cruzi by a mechanism which differs from those of classical ergosterol biosynthesis inhibitors.